Removal of Emerging Contaminants from Water by Using Carbon Materials Derived from Tingui Shells - dos Santos, Débora (2024)
This study was partly funded by the National Council for Scientific and Technological Develop-ment—CNPq (Process 200678/2022-1). Publisher Copyright: © 2024 by the authors.